2013
DOI: 10.1371/journal.pone.0078715
|View full text |Cite
|
Sign up to set email alerts
|

Human-Like Eukaryotic Translation Initiation Factor 3 from Neurospora crassa

Abstract: Eukaryotic translation initiation factor 3 (eIF3) is a key regulator of translation initiation, but its in vivo assembly and molecular functions remain unclear. Here we show that eIF3 from Neurospora crassa is structurally and compositionally similar to human eIF3. N. crassa eIF3 forms a stable 12-subunit complex linked genetically and biochemically to the 13th subunit, eIF3j, which in humans modulates mRNA start codon selection. Based on N. crassa genetic analysis, most subunits in eIF3 are essential. Subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 47 publications
6
53
1
Order By: Relevance
“…As mentioned previously, this 210-protein set consists of many proteins functioning in RNA synthesis and protein synthesis (Fig. 2D), including eIF3a and eIF3c, which were verified as two essential translation initiation factors in N. crassa (Smith et al, 2013). Such a high discordance between mRNA and protein level has previously been observed in S. cerevisiae following responses to perturbation to different stimuli (Fournier et al, 2010; Lee et al, 2011; Vogel et al, 2011).…”
Section: Resultssupporting
confidence: 66%
“…As mentioned previously, this 210-protein set consists of many proteins functioning in RNA synthesis and protein synthesis (Fig. 2D), including eIF3a and eIF3c, which were verified as two essential translation initiation factors in N. crassa (Smith et al, 2013). Such a high discordance between mRNA and protein level has previously been observed in S. cerevisiae following responses to perturbation to different stimuli (Fournier et al, 2010; Lee et al, 2011; Vogel et al, 2011).…”
Section: Resultssupporting
confidence: 66%
“…The purified S. cerevisiae 6-subunit form stimulates an in vitro initiation assay comprised of human components [50], implying that the six subunits provide most of the basic functions of eIF3 whereas the other subunits (in mammalian eIF3) may play regulatory roles, a view supported by in vivo human 3a and 3c knockdown experiments [25]. Evaluation of eIF3 in Neurospora crassa by gene deletion identified subunits a, b, c, d, f, g, i and m as essential for cell viability, whereas subunits e, h, j, k and l are dispensable [51]. Mass spectrometry provides evidence that all 13 subunits can form a complex with one copy each [52], but there remains the possibility that subcomplexes lacking one or more subunits may exist in human cells, as has been observed in S. pombe [53].…”
Section: The Structure and Assembly Of Eif3mentioning
confidence: 99%
“…When either 3a, 3b or 3c is overexpressed, the cellular level of the whole eIF3 complex rises, perhaps due to more efficient assembly. It has been suggested that a dimer of 3a and 3c forms first, onto which other subunits attach [51]. The chaperonin CCT has been shown to influence the folding of 3h and 3i by binding to 3b [71], and it is likely that still other proteins are involved in eIF3 assembly.…”
Section: The Structure and Assembly Of Eif3mentioning
confidence: 99%
“…In humans, eIF3 is the largest eIF and consists of 13 non-identical protein subunits named eIF3a to eIF3m (Damoc et al, 2007). Most other multicellular eukaroytes such as the filamentous fungus Neurospora crassa also have eIF3 complexes structurally and compositionally similar to that in humans (Smith et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Expression of recombinant human eIF3 in Escherichia coli requires all eight of the PCI-MPN-containing subunits, suggesting that the formation of the helical bundle is essential for eIF3 assembly and may be similar to either the proteasome lid or CSN (Sun et al, 2011). However, four of these eight subunits are completely dispensable in the N. crassa eIF3 complex (Smith et al, 2013), implying that eIF3 may assemble by alternative pathways that do not rely on the formation of the helical bundle in the same manner as the proteasome lid and CSN complexes. Therefore, despite recent cryo-electron microscopy (cryo-EM) reconstructions of human eIF3, the specific functions of its subunits and its cellular assembly pathway remain unclear (Aylett et al, 2015; des Georges et al, 2015; Hashem et al, 2013a; Querol-Audi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%